A polarimetric survey for dust in 47 Tucanae - Forte, Juan Carlos (2002)
We present linear polarization measurements in the V band for 77 stars in the field of the globular cluster 47 Tucanae (NGC 104) and for 14 regions free of bright stars, located along an elliptical isophotal contour of the cluster, as well as UBVRI measurements for the cluster nucleus. The observations show variable foreground polarization that, once removed, leaves marginally significant polarization residuals for the nonvariable bright red giants. Although these residuals are small, there is a systematic trend in the sense that the larger ones are seen toward the south of the cluster (in a direction opposite to that of the cluster proper motion). In contrast, most of the variable stars do show significant intrinsic polarization. The behavior of the star-free regions is similar to that of the nonvariable stars and sets an upper limit to the possible existence of a global pattern of scattered (and polarized) intracluster light in the V band. In turn, the multicolor observations of the cluster nucleus cannot be fitted with a Serkowski law and exhibit a polarization excess in both U and B. This polarization could be explained as a combination of the foreground interstellar component and another component arising from dust located in the nucleus and illuminated by a bright blue post-asymptotic giant branch star (at 48″ from the cluster center). Inspection of a set of archival Hubble Space Telescope Wide Field Planetary Camera 2 images reveals the presence of a number of dark patches in the innermost regions of the cluster. A prominent patch (some 5″ 3″ in size) located 12″ from the cluster center and with a position angle (north to east) of 120° has a slightly different polarization compared with that of the cluster nucleus and appears to be a good candidate for identification as a dust globule within the cluster.